11.2k views
1 vote
Given the equation f(x)= -10x-4 and g(x)=6-2x, find f(x) - g(x)​

User Heroic
by
5.7k points

2 Answers

4 votes


f(x) = - 10x - 4


g(x) = 6 - 2x

_________________________________


f(x) - g(x) =


( - 10x - 4) - (6 - 2x) =


- 10x - 4 - 6 + 2x =


- 8x - 10

Thus ;


f(x) - g(x) = - 8x - 10

_________________________________

And we're done.....♥️♥️♥️♥️♥️

User MusikAnimal
by
5.0k points
0 votes

Answer:

Explanation:

Given the equation f(x)= -10x-4 and g(x)=6-2x, find f(x) - g(x)​-example-1
User Crellee
by
6.7k points